Side effects and discontinuation rate of depot medroxyprogesterone acetate in a tertiary hospital, southern Nigeria - Nonye-Enyidah, Esther I.; Jumbo, Ibiebelem A.; Enyidah, Nonyenim S.; Robinson, Ebbi D.; Ejikem, Mazi Eke C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Depot medroxyprogesterone acetate (DMPA) also known as depo provera is a highly effective, safe and long-lasting reversible contraceptive with side effects that may cause discontinuation amongst acceptors. Objective was to determine the prevalence rate, side effects, discontinuation rate and indications for discontinuation of DMPA at Rivers State University Teaching Hospital (RSUTH), Port Harcourt. Methods: This was a retrospective study of 874 clients attending family planning clinic at the RSUTH from 1st January, 2015 to 31st December, 2019. Their records were retrieved from the clinic and reviewed. Data was extracted, coded and analyzed using the statistical package for social sciences (SPSS) IBM version 25.0 (Armonk, NY). Results: One hundred and one clients accepted DMPA out of 874 acceptors of contraceptives within the study period giving a prevalence rate of 11.6%. The modal age group was 25-29 years accounting for 31 (30.7%). Age range was 19-47 years and the modal parity was para 2. Majority of the clients had formal education, 100 (99%), married, 94 (93.1%) and multipara 61 (60.4%). The discontinuation rate was 32.7% and the commonest reasons for discontinuation were secondary amenorrhoea and irregular vaginal bleeding with each contributing 24.2%. Conclusions: The prevalence and discontinuation rates of Depo provera were low. Secondary amenorrhoea and irregular vaginal bleeding were the commonest side effects and reasons for discontinuation.